2022
DOI: 10.1093/nar/gkac302
|View full text |Cite
|
Sign up to set email alerts
|

“Pseudo-pseudogenes” in bacterial genomes: Proteogenomics reveals a wide but low protein expression of pseudogenes in Salmonella enterica

Abstract: Pseudogenes (genes disrupted by frameshift or in-frame stop codons) are ubiquitously present in the bacterial genome and considered as nonfunctional fossil. Here, we used RNA-seq and mass-spectrometry technologies to measure the transcriptomes and proteomes of Salmonella enterica serovars Paratyphi A and Typhi. All pseudogenes’ mRNA sequences remained disrupted, and were present at comparable levels to their intact homologs. At the protein level, however, 101 out of 161 pseudogenes suggested successful transla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 65 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…TTS profiling could reveal additional examples that are challenging to infer from the genome, such as those generated by ribosomal frameshifting. Recent MS-based proteomics analysis in Salmonella has led to the hypothesis that some pseudogenes, a hallmark of host-adapted strains, maintain full-length transcription and can likewise also show partial full-length translation, possibly via re-coding (via frameshifting or codon re-definition) mechanisms at or near the introduced nonsense mutation, to expand coding potential to provide opportunities in a more generalist niche (Feng et al, 2022). TTS profiling could, in principle, be applied to identify examples of such loci, or even - under relevant conditions - measure the ratio of full-length vs. prematurely terminated translation.…”
Section: Discussionmentioning
confidence: 99%
“…TTS profiling could reveal additional examples that are challenging to infer from the genome, such as those generated by ribosomal frameshifting. Recent MS-based proteomics analysis in Salmonella has led to the hypothesis that some pseudogenes, a hallmark of host-adapted strains, maintain full-length transcription and can likewise also show partial full-length translation, possibly via re-coding (via frameshifting or codon re-definition) mechanisms at or near the introduced nonsense mutation, to expand coding potential to provide opportunities in a more generalist niche (Feng et al, 2022). TTS profiling could, in principle, be applied to identify examples of such loci, or even - under relevant conditions - measure the ratio of full-length vs. prematurely terminated translation.…”
Section: Discussionmentioning
confidence: 99%
“…They revealed that 101 out of 161 pseudogenes could be successfully translated in S. Paratyphi A and S . Typhi (Feng et al 2022 ). Transcribed pseudogenes have also been observed in Shigella flexneri (Cervantes-Rivera et al 2020 ; Chanin et al 2019 ).…”
Section: Functional Pseudogenesmentioning
confidence: 99%
“…The comparison of pseudogenes with their functional homologs showed that most pseudogenes are truncated (480,349, 71%). Recent studies suggest that early stop codons in many truncated pseudogenes correspond to nonsense mutations (24), or transient alleles that may be reversed under purifying selection (25). Comparing the evolutionary rates of truncated and non-truncated pseudogenes we find that truncated pseudogenes are characterized by higher dN and dS, as well as higher dN/dS compared to non-truncated pseudogenes (Supplementary Figure S3), as is expected for DNA evolution following a relaxation of selection pressure (i.e., gene non-functionalization).…”
Section: Higher Density Of Pseudogenes In Plasmids Compared To Chromo...mentioning
confidence: 99%